2020
DOI: 10.1051/0004-6361/202037986
|View full text |Cite
|
Sign up to set email alerts
|

Populations of filaments from the distribution of galaxies in numerical simulations

Abstract: We present a statistical study of the filamentary structures of the cosmic web in the large hydro-dynamical simulations Illustris-TNG, Illustris, and Magneticum at redshift z = 0. We focus on the radial distribution of the galaxy density around filaments detected using the Discrete Persistent Structure Extractor (DisPerSE). We show that the average profile of filaments presents an excess of galaxy density (> 5σ) up to radial distances of 27 Mpc from the core. The relation between galaxy density and the leng… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
72
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 64 publications
(87 citation statements)
references
References 80 publications
14
72
0
Order By: Relevance
“…Filaments run from a node to a saddle point and at least two are needed to bridge between haloes. studies mentioned above, the trend of having a lower population for longer filaments seen here is widely observed in the literature (Bond, Strauss & Cen 2010;Galárraga-Espinosa et al 2020;Malavasi et al 2020;Rost et al 2020). Note also that the recovered length and number of filaments depend on the persistence level chosen during filament extraction, with a lower level leading to more nodes and a finer network.…”
Section: The Dependence Of Filament Length On the Proximity To The Central Nodesupporting
confidence: 80%
See 2 more Smart Citations
“…Filaments run from a node to a saddle point and at least two are needed to bridge between haloes. studies mentioned above, the trend of having a lower population for longer filaments seen here is widely observed in the literature (Bond, Strauss & Cen 2010;Galárraga-Espinosa et al 2020;Malavasi et al 2020;Rost et al 2020). Note also that the recovered length and number of filaments depend on the persistence level chosen during filament extraction, with a lower level leading to more nodes and a finer network.…”
Section: The Dependence Of Filament Length On the Proximity To The Central Nodesupporting
confidence: 80%
“…A similar shape is also seen in other works with different emphases and starting points, e.g. Colberg et al (2005) who used CDM numerical simulations to study the filaments between pairs of clusters, and Dolag et al (2006) who studied gas density profiles in hydrodynamical resimulations (see also Aragón-Calvo, van de Weygaert & Jones 2010; also Bonjean et al 2019;Galárraga-Espinosa et al 2020). Note, however, that the shape of the gas density profile is resolution and cooling model dependent.…”
Section: Dark Matter and Gas Characteristics Of Cluster Filamentssupporting
confidence: 77%
See 1 more Smart Citation
“…The catalogue of filaments used in this work was constructed in Galárraga-Espinosa et al (2020), which provides details and technicalities. Here, we simply summarise the main important points.…”
Section: Filament Cataloguementioning
confidence: 99%
“…In the present paper, we study gas around cosmic filaments detected with the DisPerSE algorithm (Sousbie 2011;Sousbie et al 2011) in the galaxy distribution of the Illustris The Next Generation simulation (IllustrisTNG, Nelson et al 2019) at redshift zero. We separate the gas into different density and temperature states, called phases, and we study the gas properties around the different populations of filaments identified in Galárraga-Espinosa et al (2020). We map the distribution of the different baryonic phases around filaments by building phase fraction profiles, and we characterise their thermodynamical properties by means of temperature and pressure profiles.…”
Section: Introductionmentioning
confidence: 99%